2008
DOI: 10.1111/j.1476-4431.2008.00370.x
|View full text |Cite
|
Sign up to set email alerts
|

Severe soft tissue infections in dogs: 47 cases (1996–2006)

Abstract: Objective -To describe the patient population, microbiological findings, treatment and outcome in dogs with severe soft tissue infections (SSTIs) and to compare survivors to nonsurvivors. Design -Retrospective study. Animals -Forty-seven dogs with confirmed soft tissue infections originating from the SC tissues, muscle or fascia. Interventions -None.Measurements and Main Results -Physical and clinicopathologic data on presentation, microbiological and histopathological findings, antimicrobial treatment and out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 17 publications
2
30
0
Order By: Relevance
“…Presently, there are few highly powered, large‐scale studies in the veterinary literature on which to base recommendations for using [LAC] measurements in patient evaluation and management. In an effort to provide some general guidelines, a literature search of PubMed, Scopus, and CAB Abstracts performed for this review identified 35 clinical studies that investigated [LAC] as a prognostic indicator in dogs and cats . As in the human medical literature, there was marked heterogeneity in study sizes, study populations, mortality, and selected lactate cut‐off points making comparison across studies challenging.…”
Section: Lactate As a Prognostic Indicatormentioning
confidence: 99%
See 2 more Smart Citations
“…Presently, there are few highly powered, large‐scale studies in the veterinary literature on which to base recommendations for using [LAC] measurements in patient evaluation and management. In an effort to provide some general guidelines, a literature search of PubMed, Scopus, and CAB Abstracts performed for this review identified 35 clinical studies that investigated [LAC] as a prognostic indicator in dogs and cats . As in the human medical literature, there was marked heterogeneity in study sizes, study populations, mortality, and selected lactate cut‐off points making comparison across studies challenging.…”
Section: Lactate As a Prognostic Indicatormentioning
confidence: 99%
“…Despite these limitations, the association between increased admission or initial [LAC] and mortality is well documented in dogs. From the available clinical studies that contained sufficient data for analysis, nonsurviving dogs had significantly higher [LAC] than survivors in 18 of 22 studies . Studies that found significantly higher [LAC] in nonsurvivors were in: dogs with blunt or penetrating trauma, sepsis or systemic inflammatory response syndrome (SIRS), spontaneous hemoabdomen, immune‐mediated hemolytic anemia, babesiosis, heartworm, general illness or injury, gastric dilatation and volvulus (GDV), and following cholecystectomy .…”
Section: Dogsmentioning
confidence: 99%
See 1 more Smart Citation
“…are also shed in the feces of some dogs so it is also possible that the infection was endogenous. The dog's history of immunosuppressive therapy is consistent with cases of SSTIs in the veterinary literature but is an inconsistent historical finding amongst Aeromonas ‐associated SSTIs in people. Most dogs that develop bacterial SSTIs have an underlying disease that affects their immune function or skin integrity .…”
Section: Discussionmentioning
confidence: 95%
“…Here, we report a case of severe acute panniculitis and cellulitis in a 5‐year‐old female Border Collie caused by Aeromonas spp. Although the current recommended treatment for severe soft tissue infections in both dogs and people includes aggressive surgical debridement, the patient in this case survived with medical treatment alone.…”
Section: Introductionmentioning
confidence: 95%